Ornamental towels in the traditional Bashkir culture - Baiazitova, Rozaliia R. (The New Research of Tuva, 2025)
The article analyzes the areas of application and the semantic significance of ornamented towels — “taśtamal” and “hölgö” — in the traditional culture of the Bashkirs (19th — early 20th century), where they functioned as attributes of etiquette and specific ritual practices. The sources for the study include both published and unpublished materials, among them field data collected by the author during expeditions across various regions of Bashkortostan from 2000 to 2019 and in 2024. The use of patterned towels in the interior decoration of the home contributed to the development of aesthetic taste, while the embroidery itself served as a protective amulet. Depending on the context and situation in which it was used, the towel performed various functions, which was reflected in the naming of related etiquette and ritual acts. For example, the presentation of an ornamented towel to a matchmaker by the bride’s parents signified consent to marriage; the gifting of a towel to the husband’s older male relatives (excluding his parents) marked the end of avoidance and the woman’s integration into the family. During folk celebrations, towels conveyed the festive atmosphere and fulfilled an informational role, helping to indicate the location of an event or the clan affiliation of “batyrs”, among other functions. The preparation of a gift in the form of an embroidered towel by the youngest daughter-in-law of the village for the winner of a competition during a celebration symbolized her acceptance into the new community. In the context of guest etiquette, the towel functioned as a gift of exchange, reinforcing kinship and friendly ties; in funeral and commemorative rituals, towels were presented as alms or offerings. It is noted that in recent years, changes have occurred in the production of embroidered towels, and their symbolic significance within etiquette and life-cycle rituals has been partially lost.